Deformable high-temperature alloy and preparation method thereof
By optimizing the composition and preparation process of the FE-NI-CR base deformation of high-temperature alloy, especially the addition of LA and GD rare earth elements and control process parameters, the problem of uneven alloy tissue and insufficient mechanical performance of the alloy tissue have significantly improved the uniformity of the alloy And lasting performance.
Patent Information
- Application Number
- CN202411420615.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-28
AI Technical Summary
During the preparation process of deformed high-temperature alloy materials, the structure and performance are greatly affected by the preparation process parameters, resulting in abnormal grain growth and uneven tissue, which affects the mechanical properties and corrosion resistance.
By optimizing the alloy ingredients, add LA and GD rare earth elements to reduce carbonized analysis of bias; at the same time, control the preparation process parameters, such as the vacuum and refined temperature of the vacuum sensing melting The temperature and time of processing, the strain rate and deformation of the hot -rolled treatment, the temperature and time of high temperature and low temperature heat treatment to reduce the analysis of element and improve the uniformity of the alloy tissue.
The uniformity and mechanical properties of the alloy tissue are realized, especially the durable performance of the long -term application conditions of high temperatures has been significantly improved.
Smart Images

Figure CN119372502A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-temperature alloys, and in particular relates to a deformed high-temperature alloy and a preparation method thereof. Background Art
[0002] The demand for high-temperature and corrosion-resistant materials in modern industrial manufacturing and science and technology is increasing. The Fe-Ni-Cr series of deformed high-temperature alloys have excellent comprehensive properties at high temperatures, which makes them widely used in aerospace, energy, and petrochemical fields and have great development potential. Especially in power station boiler equipment, with the improvement of unit operating parameters, high-temperature microstructure stability, high-temperature mechanical properties, oxidation resistance and corrosion resistance are more needed to meet the service requirements of key high-temperature components of high-parameter units in harsh temperature and pressure environments. However, the microstructure and properties of deformed high-temperature alloy materials are closely related to their preparation process. Therefore, the optimization of the preparation process is of great practical significance to the application and development of the Fe-Ni-Cr series of deformed high-temperature alloys.
[0003] At present, the forging and rolling process parameter window of deformed high-temperature alloys is relatively narrow, and improper forging and rolling process handling will lead to abnormal grain growth during recrystallization, resulting in oversized or fine grains. In addition, the precipitation or growth of precipitated phases affects the nucleation and grain growth during recrystallization, which in turn affects the uniformity of the deformed structure, resulting in large differences in the average grain size of the alloy, which has an adverse effect on the mechanical properties of the alloy, especially the long-term durability. Summary of the invention
[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a deformed high-temperature alloy and a preparation method thereof.
[0005] In one aspect of the present disclosure, a method for preparing a deformed high-temperature alloy is provided.
[0006] The preparation method comprises:
[0007] Ni: 45%-55%, Cr: 15%-19%, Al: 1.3%-2.2%, Ti: 1.3%-2.2%, C: ≤0.09%, Cu: ≤0.5%, B: ≤0.03%, Zr: ≤0.08%, W: ≤1.5%, Nb: ≤1.5%, Mo: ≤2%, Mn: ≤0.8%, Si: ≤0.3%, Ta: ≤1%, La: 0.5%-0.9%, Gd: 0.5%-0.9%, and the rest is Fe to form alloy raw materials;
[0008] Performing vacuum induction melting on the alloy raw material to obtain an electrode rod, and performing electroslag remelting on the electrode rod to obtain a first billet;
[0009] Performing homogenization and forging treatment on the first blank to obtain a second blank, and performing hot rolling treatment on the second blank to obtain an alloy;
[0010] The alloy is subjected to high temperature heat treatment, and after a first cooling, the alloy is subjected to low temperature heat treatment, and after a second cooling treatment, a deformed high temperature alloy is obtained.
[0011] Optionally, the power of the electroslag remelting is not greater than 250KW, the melting rate is not greater than 200kg / h, and the slag amount is 20-40Kg.
[0012] Optionally, the vacuum degree of the vacuum induction melting is lower than 30 Pa, and the refining temperature is 1350-1600°C.
[0013] Optionally, when the alloy raw materials are subjected to vacuum induction melting, Ni, Cr, Mo, Al, Ti, Nb, Fe, Zr, B, W, Si, La, and Gd are added to the vacuum induction furnace in the order of Ni, Cr, Mo, Al, Ti, and Mo, and C, Al, Ti, and Mo are added in sequence according to the sampling results.
[0014] Optionally, the temperature of the homogenization treatment is 1200° C. to 1250° C., and the time is 24 h to 48 h.
[0015] Optionally, in the forging process, the number of upsetting and drawing is 4 to 5 times, the deformation amount each time is 30 to 40%, the transfer time during the forging process is not more than 50 seconds, and the final forging temperature is not less than 800°C.
[0016] Optionally, the hot rolling treatment temperature is 1120-1200°C, and the strain rate is 15-20S -1 The deformation of each pass is not less than 20%, and the total deformation is 50% to 75%.
[0017] Optionally, the temperature of the high temperature heat treatment is 1050-1130° C., the time is 1h-2h, and the first cooling method is water quenching;
[0018] The temperature of the low temperature heat treatment is 980-1050° C., the time is 1 h-2 h, and the second cooling method is air cooling.
[0019] Another aspect of the present disclosure provides a deformed high-temperature alloy, which is prepared by the preparation method described above.
[0020] Optionally, the basic structure of the deformed high-temperature alloy is austenite, the average grain size is 109-125 μm, the grain size is level 3, and the fracture time at 700° C. and 200 MPa is 1130-1270 h.
[0021] The present invention discloses a deformed high-temperature alloy and a preparation method thereof, wherein the preparation method comprises: adding Ni: 45%-55%, Cr: 15%-19%, Al: 1.3%-2.2%, Ti: 1.3%-2.2%, C: ≤0.09%, Cu: ≤0.5%, B: ≤0.03%, Zr: ≤0.08%, W: ≤1.5%, Nb: ≤1.5%, Mo: ≤2%, Mn: ≤0.8%, Si: ≤0.3%, Ta: ≤1%, La: 0.5%
[0022] -0.9%, Gd: 0.5%-0.9%, and the rest is Fe to form an alloy raw material; vacuum induction melting is performed on the alloy raw material to obtain an electrode rod, and the electrode rod is electroslag remelted to obtain a first billet; the first billet is homogenized and forged to obtain a second billet, and the second billet is hot rolled to obtain an alloy; the alloy is subjected to high-temperature heat treatment, and after the first cooling, the alloy is subjected to low-temperature heat treatment, and after the second cooling treatment, a deformed high-temperature alloy is obtained. The present invention optimizes the alloy composition and adds La and Gd rare earth elements, which is conducive to reducing carbide segregation, making the carbides in the alloy evenly distributed and obtaining a uniform alloy structure; at the same time, by controlling the parameters of the preparation process, it is conducive to reducing element segregation and making the alloy structure more uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flowchart of a method for preparing a deformed high-temperature alloy according to an embodiment of the present disclosure;
[0024] Figure 2 The microstructure of the deformed high-temperature alloy obtained in Example 1 of the present disclosure;
[0025] Figure 3 The microstructure of the deformed high-temperature alloy obtained in Example 2 of the present disclosure;
[0026] Figure 4 The microstructure of the deformed high-temperature alloy obtained in Example 3 of the present disclosure;
[0027] Figure 5 The microstructure of the deformed high-temperature alloy obtained in Comparative Example 1 of the present disclosure;
[0028] Figure 6 The SEM morphology of the deformed high-temperature alloy obtained in Comparative Example 1 of the present disclosure;
[0029] Figure 7 is the EDS spectrum of the grain boundary precipitation phase of the deformed high-temperature alloy obtained in Comparative Example 1 of the present disclosure;
[0030] Figure 8 The microstructure of the deformed high-temperature alloy obtained in Comparative Example 2 of the present disclosure;
[0031] Fig. 9 The SEM morphology of the deformed high-temperature alloy obtained in Comparative Example 2 of the present disclosure;
[0032] Fig.10 This is the EDS spectrum of the grain boundary precipitation phase of the deformed high-temperature alloy obtained in Comparative Example 2 of the present disclosure. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the disclosure. The described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.
[0034] like Figure 1 As shown, in one aspect of the present disclosure, a method for preparing a deformed high temperature alloy is provided S100, which specifically includes the following steps S110 to S140:
[0035] S110. Ni: 45%-55%, Cr: 15%-19%, Al: 1.3%-2.2%, Ti: 1.3%
[0036] -2.2%, C: ≤0.09%, Cu: ≤0.5%, B: ≤0.03%, Zr: ≤0.08%, W: ≤1.5%,
[0037] Nb: ≤1.5%, Mo: ≤2%, Mn: ≤0.8%, Si: ≤0.3%, Ta: ≤1%, La: 0.5%
[0038] -0.9%, Gd: 0.5%-0.9%, and the rest is Fe, forming alloy raw materials.
[0039] In this embodiment, the content of Fe, Ni, and Cr components in the raw material is relatively high, forming a Fe-Ni-Cr alloy. By optimizing the alloy components, an alloy with a uniform structure can be obtained, which effectively improves the mechanical properties of the alloy and meets the application requirements of high temperature and long time. Among them, Fe is low in price, which is conducive to reducing costs, and the Fe element can significantly improve the deformation ability of the alloy and reduce the risk of alloy forging cracking.
[0040] Secondly, in this embodiment, by optimizing the addition of La and Gd rare earth elements in the alloy composition, since the above elements exist at the grain boundaries in the state of solid solution atoms, their special peripheral atomic arrangement can interact strongly with other elements in the alloy, making it difficult for carbides to precipitate at the grain boundaries, achieving the regulation of carbides at the grain boundaries, thereby reducing the segregation of carbides and making the carbides in the alloy uniformly distributed. In addition, La and Gd rare earth elements can also reduce the segregation of elements such as S, P, and O at the grain boundaries. These precipitated carbides and inclusions can pin dislocations, hinder the migration and slip of dislocations, and have an inhibitory effect on the recovery of grains. Therefore, La and Gd rare earth elements are beneficial to reducing the segregation of carbides and inclusions, thereby facilitating the acquisition of uniform alloy structure.
[0041] S120, performing vacuum induction melting on the alloy raw material to obtain an electrode rod, and performing electroslag remelting on the electrode rod to obtain a first billet.
[0042] Specifically, the alloy raw material of step S110 is loaded into a vacuum induction furnace, and the alloy is heated and smelted under high vacuum conditions to obtain an electrode rod, which is then subjected to a peeling process to remove surface defects and obtain a smooth surface. Thereafter, the electrode rod is electroslag remelted to obtain a first billet.
[0043] It should be understood that the alloy raw materials need to be free of oil and oxide scale before smelting, and added into the vacuum induction furnace in the order of Ni, Cr, Mo, AI, Ti, Nb, Fe, Zr, B, W, Si, La, and Gd. Samples are taken 2-3 times during the smelting process, and C, Al, Ti, Mo, etc. are added in sequence according to the sampling results.
[0044] In some preferred embodiments, the vacuum degree of vacuum induction melting is lower than 30Pa, and the refining temperature is 1350-1600°C. For example, the vacuum degree is preferably 28Pa, 25Pa, 20Pa, 15Pa, etc., and the temperature is preferably 1350°C, 1380°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C.
[0045] In other preferred embodiments, the power of electroslag remelting is not more than 250KW, the melting rate is not more than 200kg / h, and the slag amount is 20-40Kg. For example, the power is preferably 240KW, 200KW, 180KW, 150KW, etc., the melting rate is preferably 180kg / h, 170kg / h, 160kg / h, 150kg / h, etc., and the amount of electroslag remelted is preferably 20Kg, 25Kg, 30Kg, 35Kg, etc.
[0046] It should be understood that the degree of dendrite segregation and the size of the dendrite spacing during the smelting process are directly related to the cooling rate of the alloy solution. Therefore, in this embodiment, the cooling rate is increased by controlling the power and melting rate during the alloy smelting process, thereby reducing dendrite segregation.
[0047] S130, performing homogenization and forging treatments on the first billet to obtain a second billet, and performing hot rolling treatment on the second billet to obtain an alloy.
[0048] Specifically, the first blank obtained in step S120 is homogenized at 1200°C to 1250°C for 24h to 48h, and then subjected to upsetting and drawing forging to obtain a forged second blank. The second blank is then hot rolled at 1120 to 1200°C and a strain rate of 15 to 20S -1 The deformation of each pass is not less than 20%, and the total deformation is 50% to 75%.
[0049] In some preferred embodiments, during the forging process, the number of upsetting and drawing is 4 to 5 times, the deformation amount each time is 30 to 40%, the transfer time during the forging process is no more than 50 seconds, and the final forging temperature is no less than 800°C.
[0050] As a further preferred solution, the number of upsetting and drawing is preferably 4 or 5 times, the deformation amount each time is 30%, 40%, the transfer time is preferably 45s, 40s, 35s, etc., and the final forging temperature is preferably 800°C, 850°C, 900°C, etc.
[0051] It should be noted that the forging in this embodiment can use hammer and anvil preheating and soft sheath material to reduce temperature drop to prevent excessive deformation resistance caused by precipitation strengthening phase precipitation.
[0052] In some other preferred embodiments, the hot rolling process includes an initial rolling process and a final rolling process, wherein the temperature of the initial rolling process is 1170-1200°C, and the temperature of the final rolling process is 1120-1150°C.
[0053] In this embodiment, high-temperature homogenization at a higher temperature can eliminate the low-melting point phase existing in the ingot and reduce the element dendrite segregation. In addition, increasing the forging ratio and rolling deformation can also effectively reduce the element segregation and make the alloy structure more uniform.
[0054] S140, subjecting the alloy to high temperature heat treatment, subjecting the alloy to low temperature heat treatment after the first cooling, and subjecting the alloy to a second cooling treatment to obtain a deformed high temperature alloy.
[0055] In some preferred embodiments, the temperature of the high temperature heat treatment is 1050-1130°C, the time is 1h-2h, and the first cooling method is water quenching. For example, the temperature of the high temperature heat treatment is preferably 1050°C, 1060°C, 1090°C, 1110°C, 1120°C, 1130°C, etc., and the time is preferably 1h, 1.5h, 2h, etc.
[0056] In other preferred embodiments, the temperature of the low temperature heat treatment is 980-1050°C, the time is 1h-2h, and the second cooling method is air cooling. For example, the temperature of the low temperature heat treatment is preferably 980°C, 990°C, 1000°C, 1010°C, 1030°C, 1050°C, etc., and the time is preferably 1h, 1.5h, 2h, etc.
[0057] The preparation process of this embodiment is simple. Through comprehensive means such as smelting, forging, rolling, high temperature / low temperature heat treatment, the problem of uneven structure, especially the influence of carbide precipitation on structure uniformity, is solved, making the alloy structure more uniform, thereby improving the long-term creep performance of the alloy (i.e., mechanical properties under high temperature / stress coupling).
[0058] Another aspect of the present disclosure provides a deformed high-temperature alloy prepared by the preparation method described above.
[0059] In some preferred embodiments, the basic structure of the deformed high-temperature alloy is austenite, the average grain size is 109-125 μm, the grain size is level 3, and the fracture time at 700° C. and 200 MPa is 1130-1270 h.
[0060] The preparation method and properties of the deformed high temperature alloy will be further described below in conjunction with specific examples:
[0061] Example 1
[0062] The method for preparing the deformed high temperature alloy in this example includes the following steps:
[0063] S1. The alloy raw materials are prepared according to the following proportions: Ni: 46%, Cr: 19%, Al: 1.7%, Ti: 1.9%, C: 0.08%, Cu: 0.2%, B: 0.01%, Zr: 0.05%, W: 1.0%, Nb: 1.2%, Mo: 0.7%, Mn: 0.3%, Si: 0.2%, Ta: 0.03%, La: 0.6%, Gd: 0.6%, and the rest is Fe.
[0064] S2. The above alloy raw materials are loaded into a vacuum induction furnace with a pre-vacuum of 28Pa and a refining temperature of 1500°C. The alloy is heated and melted to obtain an electrode rod, and the electrode rod is peeled and the defects are removed to obtain a smooth surface. The electrode is electroslag remelted to obtain a second billet, wherein the power is 240KW, the melting rate is 180kg / h, and the slag amount is 20Kg.
[0065] S3. The first billet is homogenized at 1210℃ for 48h, and then upsetting and drawing are performed to obtain the second billet after forging. During the forging process, the hammer anvil is preheated and the soft package material is used to reduce the temperature drop. The transfer time is 45s, and the final forging temperature is 850℃. The upsetting and drawing times are 4 times, and the deformation amount each time is 40%. The second billet is then hot rolled to obtain the alloy, wherein the strain rate during the hot rolling process is 20S -1 The initial rolling temperature is 1200℃, the final rolling temperature is 1150℃, the deformation amount of each pass is 20%, and the total deformation amount is 60%.
[0066] S4. Perform high-temperature heat treatment on the alloy, the heat treatment temperature is 1130°C, the heat treatment time is 1.5h, and the cooling method is water quenching; perform low-temperature heat treatment on the alloy, the heat treatment temperature is 1030°C, the heat treatment time is 1.5h, and the cooling method is air cooling to obtain a deformed high-temperature alloy.
[0067] Furthermore, in this embodiment 1, copper sulfate solution is used to display the structure of the alloy. Figure 2 The alloy structure morphology obtained in Example 1 has a matrix structure of austenite, an average grain size of 117um, a grain size of level 3, and good uniformity.
[0068] Furthermore, as shown in Table 1, a durability test was conducted on it under the conditions of 700°C and 200 MPa, and the fracture time was 1270 h, indicating good durability.
[0069] Example 2
[0070] The method for preparing the deformed high temperature alloy in this example includes the following steps:
[0071] S1. The alloy raw materials are prepared according to the following proportions: Ni: 54%, Cr: 16%, Al: 2.1%, Ti: 2.2%, C: 0.03%, Cu: 0.1%, B: 0.03%, Zr: 0.03%, W: 0.7%, Nb: 1.0%, Mo: 0.3%, Mn: 0.2%, Si: 0.1%, Ta: 0.08%, La: 0.8%, Gd: 0.8%, and the rest is Fe.
[0072] S2. The alloy raw materials are loaded into a vacuum induction furnace with a pre-vacuum of 25Pa and a refining temperature of 1380°C. The alloy is heated and melted to obtain an electrode rod, which is peeled to remove defects and obtain a smooth surface. The electrode is electroslag remelted to obtain the first billet, wherein the power is 180KW, the melting rate is 160kg / h, and the slag amount is 25Kg.
[0073] S3. The first billet is homogenized at 1250℃ for 24h, and then upsetting and drawing are performed to obtain the second billet after forging. During the forging process, the hammer anvil is preheated and the soft jacket material is used to reduce the temperature drop. The transfer time is 45s, and the final forging temperature is 850℃. The upsetting and drawing times are 4 times, and the deformation amount each time is 30%. The second billet is then hot rolled to obtain the alloy, wherein the strain rate during the hot rolling process is 15S -1 The initial rolling temperature is 1200℃, the final rolling temperature is 1130℃, the deformation amount of each pass is 25%, and the total deformation amount is 75%.
[0074] S4. Perform high-temperature heat treatment on the alloy, the heat treatment temperature is 1060°C, the heat treatment time is 1.5h, and the cooling method is water quenching; perform low-temperature heat treatment on the alloy, the heat treatment temperature is 1000°C, the heat treatment time is 1.5h, and the cooling method is air cooling to obtain a deformed high-temperature alloy.
[0075] Furthermore, in this embodiment 2, copper sulfate solution is used to display the structure of the alloy. Figure 3 This is the alloy structure morphology obtained in Example 2, wherein the matrix structure is austenite, the average grain size is 125 μm, the grain size is level 3, and it has good uniformity.
[0076] Furthermore, as shown in Table 1, a durability test was conducted on it under the conditions of 700°C and 200 MPa, and the fracture time was 1130 h, indicating good durability.
[0077] Example 3
[0078] The method for preparing the deformed high temperature alloy in this example includes the following steps:
[0079] S1. The alloy raw materials are prepared according to the following proportions: Ni: 54%, Cr: 18%, Al: 1.5%, Ti: 1.5%, C: 0.06%, Cu: 0.4%, B: 0.01%, Zr: 0.02%, W: 1.3%, Nb: 1.2%, Mo: 0.8%, Mn: 0.3%, Si: 0.2%, Ta: 0.04%, La: 0.9%, Gd: 0.9%, and the rest is Fe.
[0080] S2. The above alloy raw materials are loaded into a vacuum induction furnace with a pre-vacuum of 28Pa and a refining temperature of 1450°C. The alloy is heated and melted to obtain an electrode rod, and the electrode rod is peeled and the defects are removed to obtain a smooth surface. The electrode is electroslag remelted to obtain a second billet, wherein the power is 200KW, the melting rate is 170kg / h, and the slag amount is 30Kg.
[0081] S3. The first billet is homogenized at 1230℃ for 36h, and then upsetting and drawing are performed to obtain the second billet after forging. During the forging process, the hammer anvil is preheated and the soft package material is used to reduce the temperature drop. The transfer time is 40s, and the final forging temperature is 800℃. The upsetting and drawing times are 5 times, and the deformation amount each time is 40%. The second billet is then hot rolled to obtain the alloy, wherein the strain rate during the hot rolling process is 20S -1 The initial rolling temperature is 1170℃, the final rolling temperature is 1120℃, the deformation amount of each pass is 20%, and the total deformation amount is 60%.
[0082] S4. Perform high-temperature heat treatment on the alloy, the heat treatment temperature is 1060°C, the heat treatment time is 2h, and the cooling method is water quenching; perform low-temperature heat treatment on the alloy, the heat treatment temperature is 980°C, the heat treatment time is 2h, and the cooling method is air cooling to obtain a deformed high-temperature alloy.
[0083] Furthermore, in this embodiment 3, copper sulfate solution is used to display the structure of the alloy. Figure 4 The alloy structure morphology obtained in Example 3 has a matrix structure of austenite, an average grain size of 109um, a grain size of level 3, and good uniformity.
[0084] Furthermore, as shown in Table 1, a durability test was conducted on it under the conditions of 700°C and 200 MPa, and the fracture time was 1231 h, indicating good durability.
[0085] Comparative Example 1
[0086] The method for preparing the deformed high temperature alloy in this example includes the following steps:
[0087] S1. The alloy raw materials are prepared according to the following proportions: Ni: 46%, Cr: 19%, Al: 1.7%, Ti: 1.9%, C: 0.08%, Cu: 0.2%, B: 0.01%, Zr: 0.05%, W: 1.0%, Nb: 1.2%, Mo: 0.7%, Mn: 0.3%, Si: 0.2%, Ta: 0.03%, and the rest is Fe.
[0088] S2. The above alloy raw materials are loaded into a vacuum induction furnace with a pre-vacuum of 28Pa and a refining temperature of 1500°C. The alloy is heated and melted to obtain an electrode rod, and the electrode rod is peeled and the defects are removed to obtain a smooth surface. The electrode is electroslag remelted to obtain a second billet, wherein the power is 240KW, the melting rate is 180kg / h, and the slag amount is 20Kg.
[0089] S3. The first billet is homogenized at 1210℃ for 48h, and then upsetting and drawing are performed to obtain the second billet after forging. During the forging process, the hammer anvil is preheated and the soft package material is used to reduce the temperature drop. The transfer time is 45s, and the final forging temperature is 850℃. The upsetting and drawing times are 2 times, and the deformation amount each time is 40%. The second billet is then hot rolled to obtain the alloy, wherein the strain rate during the hot rolling process is 20S -1 The initial rolling temperature is 1200℃, the final rolling temperature is 1150℃, the deformation amount of each pass is 10%, and the total deformation amount is 30%.
[0090] S4. Perform high-temperature heat treatment on the alloy, the heat treatment temperature is 1130°C, the heat treatment time is 1.5h, and the cooling method is water quenching; perform low-temperature heat treatment on the alloy, the heat treatment temperature is 1030°C, the heat treatment time is 1.5h, and the cooling method is air cooling to obtain a deformed high-temperature alloy.
[0091] Furthermore, in this comparative example 1, copper sulfate solution was used to perform microstructure analysis on the alloy. Figure 5 The alloy structure morphology obtained in Comparative Example 1 has poor uniformity and shows a large number of small grains. The SEM morphology of the grains is characterized, and the results are as follows: Figure 6 As shown in Figure 2, it can be seen that there is obvious precipitation pinning at the grain boundary, and the corresponding EDS spectrum is shown in Figure 2. Figure 7 As shown, its composition analysis shows that the precipitated phase is Ti-rich MX phase, so the element segregation in the preparation process has an adverse effect on the uniformity of the alloy structure.
[0092] Furthermore, as shown in Table 1, the alloy was subjected to a durability test at 700°C and 200 MPa, and the fracture time was 549 h, indicating that the uneven structure significantly reduced the durability of the alloy.
[0093] Comparative Example 2
[0094] The method for preparing the deformed high temperature alloy in this example includes the following steps:
[0095] S1. The alloy raw materials are prepared according to the following ratios: Ni: 54%, Cr: 16%, Al: 2.1%, Ti: 2.2%, C: 0.03%, Cu: 0.1%, B: 0.03%, Zr: 0.03%, W: 0.7%, Nb: 1.0%, Mo: 0.3%, Mn: 0.2%, Si: 0.1%, Ta: 0.08%, and the rest is Fe.
[0096] S2. The alloy raw materials are loaded into a vacuum induction furnace with a pre-vacuum of 25Pa and a refining temperature of 1380°C. The alloy is heated and melted to obtain an electrode rod, and the electrode rod is peeled and the defects are removed to obtain a smooth surface. The electrode is electroslag remelted to obtain a second billet, wherein the power is 380KW, the melting rate is 260kg / h, and the slag amount is 25Kg.
[0097] S3. The first billet is homogenized at 1250℃ for 24h, and then upsetting and drawing are performed to obtain the second billet after forging. During the forging process, the hammer anvil is preheated and the soft jacket material is used to reduce the temperature drop. The transfer time is 45s, and the final forging temperature is 850℃. The upsetting and drawing times are 4 times, and the deformation amount each time is 30%. The second billet is then hot rolled to obtain the alloy, wherein the strain rate during the hot rolling process is 15S -1 The initial rolling temperature is 1200℃, the final rolling temperature is 1130℃, the deformation amount of each pass is 25%, and the total deformation amount is 75%.
[0098] S4. Perform high-temperature heat treatment on the alloy, the heat treatment temperature is 1060°C, the heat treatment time is 1.5h, and the cooling method is water quenching; perform low-temperature heat treatment on the alloy, the heat treatment temperature is 1000°C, the heat treatment time is 1.5h, and the cooling method is air cooling to obtain a deformed high-temperature alloy.
[0099] Furthermore, in this comparative example 2, copper sulfate solution was used to perform microstructure analysis on the alloy. Figure 8 The alloy structure morphology obtained in Comparative Example 2 has poor uniformity and shows a large number of small grains. The SEM morphology of the grains is characterized, and the results are as follows: Fig. 9 As shown in Figure 2, it can be seen that there is obvious precipitation pinning at the grain boundary, and the corresponding EDS spectrum is shown in Figure 2. Fig.10 As shown, its composition analysis shows that the precipitated phase is Ti-rich MX phase, so the element segregation in the preparation process has an adverse effect on the uniformity of the alloy structure.
[0100] Furthermore, as shown in Table 1, the alloy was subjected to a durability test at 700°C and 200 MPa, and the fracture time was 682 h, indicating that the uneven structure significantly reduced the durability of the alloy.
[0101] Table 1 The durability performance results of the alloys obtained from Examples 1-3 and Comparative Examples 1-2
[0102] Test temperature stress Break time Example 1 700℃ 250MPa 1270h Example 2 700℃ 250MPa 1130h Example 3 700℃ 250MPa 1231h Comparative Example 1 700℃ 250MPa 549h Comparative Example 2 700℃ 250MPa 682h
[0103] In summary, according to the results of Examples 1-3 and Comparative Examples 1-2, when La and Gd are not included in the alloy components, the power and melting rate of the electroslag remelting are large, or the number of forging times is small and the hot rolling deformation is small, the uniformity of the formed alloy structure is poor, which leads to poor durability and easy breakage.
[0104] The present disclosure proposes a deformed high-temperature alloy and a preparation method thereof, which have the following beneficial effects compared with the prior art: the present disclosure optimizes the alloy composition and adds La and Gd rare earth elements, which is beneficial to reducing carbide segregation, making the carbides in the alloy evenly distributed and obtaining a uniform alloy structure; at the same time, the present disclosure also optimizes the preparation process and controls the preparation process parameters, which is beneficial to reducing element segregation and making the alloy structure more uniform. For example, by controlling the power and melting rate in the alloy smelting process, the cooling rate is increased and the dendrite segregation is reduced; secondly, by increasing the homogenization temperature, the low-melting point phase existing in the ingot is eliminated and the element dendrite segregation is reduced; furthermore, by increasing the forging ratio and the rolling deformation amount, the element segregation can also be effectively reduced, making the alloy structure more uniform, and further improving the long-term durability of the mechanical properties of the alloy.
[0105] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.
Claims
1. A method for preparing a deformed high-temperature alloy, characterized in that: The preparation method comprises: Ni: 45%-55%, Cr: 15%-19%, Al: 1.3%-2.2%, Ti: 1.3%-2.2%, C: ≤0.09%, Cu: ≤0.5%, B: ≤0.03%, Zr: ≤0.08%, W: ≤1.5%, Nb: ≤1.5%, Mo: ≤2%, Mn: ≤0.8%, Si: ≤0.3%, Ta: ≤1%, La: 0.5%-0.9%, Gd: 0.5%-0.9%, and the rest is Fe to form alloy raw materials; Performing vacuum induction melting on the alloy raw material to obtain an electrode rod, and performing electroslag remelting on the electrode rod to obtain a first billet; Performing homogenization and forging treatment on the first blank to obtain a second blank, and performing hot rolling treatment on the second blank to obtain an alloy; The alloy is subjected to high temperature heat treatment, and after a first cooling, the alloy is subjected to low temperature heat treatment, and after a second cooling treatment, a deformed high temperature alloy is obtained.
2. The preparation method according to claim 1, characterized in that: The power of the electroslag remelting is not more than 250KW, the melting speed is not more than 200kg / h, and the slag amount is 20-40Kg.
3. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum induction melting is lower than 30 Pa, and the refining temperature is 1350-1600°C.
4. The preparation method according to claim 1, characterized in that: When the alloy raw materials are subjected to vacuum induction melting, Ni, Cr, Mo, Al, Ti, Nb, Fe, Zr, B, W, Si, La, and Gd are added into the vacuum induction furnace in the order, and C, Al, Ti, and Mo are added in sequence according to the sampling results.
5. The preparation method according to claim 1, characterized in that: The temperature of the homogenization treatment is 1200° C. to 1250° C., and the time is 24 h to 48 h.
6. The preparation method according to claim 1, characterized in that: In the forging process, the number of upsetting and drawing is 4 to 5 times, the deformation amount of each time is 30 to 40%, the transfer time during the forging process is not more than 50 seconds, and the final forging temperature is not less than 800°C.
7. The preparation method according to claim 1, characterized in that: The temperature of the hot rolling treatment is 1120-1200°C, and the strain rate is 15-20S -1 The deformation of each pass is not less than 20%, and the total deformation is 50% to 75%.
8. The preparation method according to claim 1, characterized in that: The temperature of the high temperature heat treatment is 1050-1130°C, the time is 1h-2h, and the first cooling method is water quenching; The temperature of the low temperature heat treatment is 980-1050° C., the time is 1 h-2 h, and the second cooling method is air cooling.
9. A deformed high temperature alloy, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. The deformed high temperature alloy according to claim 9, characterized in that: The basic structure of the deformed high-temperature alloy is austenite, the average grain size is 109-125 μm, the grain size is level 3, and the fracture time at 700° C. and 200 MPa is 1130-1270 h.